Private capital flows, stock market and economic growth in developed and developing countries: a comparative analysis - Choong, Chee Keong; Baharumshah, Ahmad Zubaidi; Yusop, Zulkornain; Habibullah, Muzafar Shah (Elsevier, 2010)
Empirically we investigate how three types of private capital flows could promote economic growth in recipient developed and developing countries. Our focus is on the role of stock markets as a channel through which foreign capital flows could promote growth. The findings reveal that FDI exhibits a positive impact on growth, while both foreign debt and portfolio investment have a negative impact on growth in all sample countries. However, our results indicate that stock markets might be a significant channel or leading institutional factor through which capital flows affect economic growth. The findings provide clear implications that the negative impact of private capital flows can be transformed into a positive one if the stock market development has attained a certain threshold level, regardless of whether it is in developed or developing countries.